PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT TELENET KOTA TANGERANG - Ananda Okta Mahardhika; Komarudin (Journal of Research and Publication Innovation, 2025)
This research is titled “The Influence of Motivation and Work Discipline on Employee Performance at PT TeleNet Kota Tangerang”. This study aims to determine the influence of motivation and discipline on employee performance at PT TeleNet Kota Tangerang. This type of research is quantitative. The analysis methods used in this study are validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, t-tests and F-tests. The population in this study is employees of PT TeleNet Kota Tangerang using a saturated sample, which is 62 respondents. The results of this study based on the determination coefficient show that Motivation and Discipline have a contribution to Employee Performance of 0.726 or 72.6% while the remaining 27.4% are other variables that are not studied. The results showed that the multiple linear regression equation Y = 6.971 + 0.215 X1 + 0.570 X2. The value of the correlation coefficient of Motivation (X1) to Performance (Y) is 0.759, which means that the two variables have a strong level of relationship, the coefficient value of Incentive (X2) to Performance (Y) is 0.707, which means that both variables have a strong level of relationship. The results of the simultaneous influence of the independent variable on the bound variable were obtained with a value of Fcal = 78.101 > a value of Ftable = 3.15, so that it can be concluded that partially or simultaneously there is an influence between Motivation and Discipline on Employee Performance of PT TeleNet Kota Tangerang.